A REVIEW OF THE PHTHITIA OF THE JUAN FERNANDEZ ISLANDS, WITH DESCRIPTIONS OF4 NEW FLIGHTLESS SPECIES FROM ROBINSON CRUSOE ISLAND. (DIPTERA: SPHAEROCERIDAE) (Acta Entomológica Chilena, 2022)
The seven strap-winged species of Phthitia Enderlein endemic to the Juan Fernandez Islands are reviewed, with the description of four new species: P. gonzalezi, P. charpentieri, P. miradorensis, and P. cortesi. A key is provided to all species of brachypterous Sphaeroceridae known from the Juan Fernandez Islands. The phylogenetic relationships between the species of the Phthitia venosa group are discussed.